Disturbance of glutamate metabolism and inhibition of CaM-CaMKII-CREB signaling pathway in the hippocampus of mice induced by 1, 2-dichloroethane exposure. (1st October 2022) - Huang, Weiyu; Wang, Zijiang; Wang, Gaoyang; Li, Kunyang; Jin, Yaping; Zhao, Fenghong
Abstract: 1, 2-Dichloroethane (1, 2-DCE) is a highly toxic neurotoxicity, and the brain tissue is the main target organ. At present, long-term exposure to 1, 2-DCE has been shown to cause cognitive dysfunction in some studies, but the mechanism is not clear. The results of this study showed that long-term 1, 2-DCE exposure decreased learning and memory abilities in mice and impaired the structure and morphology of neurons in the hippocampal region. Moreover, except for the mRNA level of PAG, the enzymatic activities and protein levels of GS and PAG, as well as the mRNA level of GS were inhibited. With increasing dose of exposure, the protein and mRNA expression of GLAST and GLT-1 also decreased. Contrarily, there were protein and mRNA expression upregulation of GluN1, GluN2A and GluN2B in the hippocampus, as well as increased levels of extracellular Glu and intracellular Ca 2+ . In addition, 1, 2-DCE exposure also downregulated the protein expression levels of CaM, CaMKII and CREB. Taken together, our results suggest that long-term 1, 2-DCE exposure impairs the learning and memory capacity in mice, which may be attributed to the disruption of Glu metabolism and the inhibition of CaM- CaMKII-CREB signaling pathway in the hippocampus. Graphical abstract: Image 1 Highlights: 1, 2-DCE exposure can cause learning and memory impairment in mice. Glu metabolism and transport are disrupted by 1, 2-DCE. Over-activation of NMDARs and calcium overload may lead to neuronal damage. Inhibition of CaM- CaMKII-CREB pathway may be involved in cognitive disorders.